Electrochemical Removal of Cesium Ions via Capacitive Deionization Using an Ion-Exchange Layer Coated on a Carbon Electrode - Sang-Hun Lee (MDPI AG, 2021)
This study was conducted to evaluate the feasibility of using electrosorption to remove cesium (Cs+) ions from aqueous solutions using the membrane capacitive deionization (MCDI) process. The electrochemical properties were analyzed using cyclic voltammetry (CV) and impedance spectroscopy (EIS). The activated carbon electrode coated by a polymer layer showed higher specific adsorption capacity (SAC) and removal efficiency of Cs+ than the AC electrode. The effects of potential, flow rate, initial Cs+ concentration, and pH values were investigated to optimize the electrosorption performance. The electrosorption capacity increased with an increase in the applied potential and the concentration of Cs+ in the influent water. The pH value is an important parameter on electrosorption performance. The removal of Cs+ ions was affected by the pH of the influent water because H+ ions acted as competing ions during the electrosorption process. Cs+ was preferentially adsorbed to the electrode in the early stages of adsorption but was later replaced by H+. A higher presence of H+ ions could reduce the adsorption capacity of Cs+ ions. The ion-exchange layer coated AC electrode was shown to be favorable for the removal of Cs+, despite the limited electrosorption ability in a highly acidic solution.